Model electrocatalysts for the oxidation of rechargeable electrofuels - carbon supported Pt nanoparticles prepared in UHV. (1st September 2021) - Stumm, Corinna; Kastenmeier, Maximilian; Waidhas, Fabian; Bertram, Manon; Sandbeck, Daniel J.S.; Bochmann, Sebastian; Mayrhofer, Karl J.J.; Bachmann, Julien; Cherevko, Serhiy; Brummel, Olaf; Libuda, Jörg
Abstract: Isopropanol (IPA) can be used as a rechargeable electrofuel. In this approach, IPA is oxidized to acetone (ACE) in a direct alcohol fuel cell and the formed ACE is subsequently back-converted to IPA in a heterogeneously catalyzed process. To study the electrochemical reaction mechanisms of the IPA oxidation at the molecular level, appropriate and well-defined model electrocatalysts are necessary. In this work we prepare such model electrocatalysts by surface science methods in ultra-high vacuum (UHV). The catalysts consist of well-defined platinum nanoparticles on carbon supports. As carbon support, we use flat highly ordered pyrolytic graphite (HOPG) and thin (20 nm) magnetron sputtered carbon films on a polycrystalline gold substrate. In a first step, we characterize the model electrocatalysts and investigate their stability in-situ with complementary methods, i.e. by electrochemical scanning tunneling microscopy (EC-STM), electrochemical on-line inductively coupled plasma mass spectrometry (ICP-MS) and CO stripping experiments followed by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We determined a stability window ranging from -0.65 VRHE to 1.15 VRHE for both sample types, independent of the presence or absence of IPA in the electrolyte. In the second step, we study the oxidation of IPA on tPt nanoparticles using differential electrochemical mass spectrometry (DEMS) and EC-IRRAS. The onset of IPA oxidation is observed at 0.3 VRHE . ACE is formed with high selectivity, while we identify traces of CO2 as the only side-product formed at higher potentials. However, we do not observe any formation of adsorbed CO. A direct comparison of these results with previous work on Pt(111) suggests that low coordinated Pt sites and size effects play a subordinate role for IPA oxidation on Pt electrocatalysts. Graphical Abstract: Image, graphical abstract